2001
DOI: 10.2514/2.5743
|View full text |Cite
|
Sign up to set email alerts
|

Reaction and Mixing-Controlled Combustion in Scramjet Engines

Abstract: H 2 -fueled scramjet engines were tested under Mach 4 (M4) to Mach 8 (M8) ight conditions, and the local equivalence ratio and combustion ef ciency were measured by gas sampling at the engine exit. Correlation between the local values of equivalence ratio and combustion ef ciency showed that the M4 combustion was principally reaction controlled and the reaction and the mixing-controlled combustion coexisted in the M6 condition. The M8 combustion in the engines was rate controlled by the mixing of H 2 . Compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(22 citation statements)
references
References 13 publications
2
20
0
Order By: Relevance
“…The flame index and the OH radical distributions in our simulations indicates that a reaction rate controlled combustion in the weak mode, and a mixing rate controlled combustion in the intensive mode. Our simulations qualitatively reproduce the gas sampling measurement at the exit plane [4]. Thus, our simulation captured not only the mode transition point, but also the flame structures at each combustion mode.…”
Section: B Flame Structures In Weak-and Intensive-combustion Modessupporting
confidence: 58%
See 3 more Smart Citations
“…The flame index and the OH radical distributions in our simulations indicates that a reaction rate controlled combustion in the weak mode, and a mixing rate controlled combustion in the intensive mode. Our simulations qualitatively reproduce the gas sampling measurement at the exit plane [4]. Thus, our simulation captured not only the mode transition point, but also the flame structures at each combustion mode.…”
Section: B Flame Structures In Weak-and Intensive-combustion Modessupporting
confidence: 58%
“…Mitani et al [4] conducted the gas sampling measurement at the exit of the engine for each of the modes. The gas sampling data showed that a reaction rate controlled combustion in the weak mode, and a mixing rate of fuel controlled combustion in the intensive mode.…”
Section: B Flame Structures In Weak-and Intensive-combustion Modesmentioning
confidence: 99%
See 2 more Smart Citations
“…We sampled gas at the exit of the combustor using a water-cooled sampling probe to evaluate the local equivalence ratio and combustion efficiency. The probe ensured reaction quenching during sampling [28]. There were 63 sampling points with an interval of 10 mm (9 points in the height direction x 7 in the width direction).…”
Section: E Gas Sampling Measurementmentioning
confidence: 99%